The effects of sugar production, domestic sugar consumption and real effective exchange rate to sugar exports of the Philippines, 1977-2011 - Benedicto, Monique B. Saligumba, Arlie A. and Seville, Miqhaela Janna P. 4 0 16; 5
u
Undergraduate Thesis: (BS in Business Economics)-Pamantasan ng Lungsod ng Maynila , 2013.
Keywords: 2 -- 0; 6; 20; 20; 2